Clinical and demographic profile of adult patients subjected to an assessment of arterial hypertension with an ambulatory blood pressure monitoring device. EPEDMAPA Registry (2019)
Introduction: Arterial hypertension is a public health problem that increases mortality in all clinical situations. It is also the main modifiable risk factor. It is a highly prevalent condition that is suffered by around 25% of the world population. Few patients are aware of it, and few receive the optimum treatment. Objective: To evaluate the characteristics of the patients on whom ambulatory blood pressure monitoring was carried out in a University Hospital, with a view to describing the clinical and demographic profile. Methods: A descriptive retrospective study was conducted on patients subjected to 24-hour ambulatory blood pressure monitoring, during the months of October and December 2015. Results: Hypertension (recently diagnosed or known) was confirmed in 75% of the studies performed. Arterial hypertension was ruled out in 31% of the patients previously classified as hypertensive. Of the patients that were receiving treatment, 61% were well-controlled, with the majority of them with a single drug, mainly an angiotensin II receptor agonist. The dipper was most prevalent circadian pattern, with 48%, followed by the non-dipper pattern in 29%. Conclusions: Ambulatory blood pressure monitoring helps in the evaluation of the blood pressure status accurately in patients with a suspicion of arterial hypertension. This clarifies whether the patients are really normotensive or hypertensive and discriminates between the “white coat” and masked hypertension conditions. This avoids unnecessary treatments and favours a better control of the blood pressure. © 2019